The Effect of Financial Literacy and Financial Management on SME Business Performance in Gowa Regency - Nurul Ilmi; Abdul Muttalib; A. Tenri Syahriani (International Journal of Economic Research and Financial Accounting, 2024)
The purpose of this study is a type of quantitative research with the aim of determining the effect of financial literacy and financial management on the business performance of SMEs in Gowa Regency. This sample was taken as many as 51 respondents from the number of SMEs without limiting those registered in Disperindag Gowa. The type of data used in this study is quantitative data obtained from questionnaires distributed to SMEs and related to the problem under study. Data collection is carried out by observation and distribution of questionnaires. In this study, the data source used in data collection is primary data. The research instrument used in this study used the Likert scale. Based on the results of data research using the Statistical Package for the Social Science (SPSS) version 29 regarding the influence of financial literacy and financial management on SME business performance in Gowa Regency which has been discussed from the previous chapter, the author draws an important conclusion, namely financial literacy and financial management have a positive and significant effect on SME business performance.